Droplet‐Based Microfluidics Platform for the Synthesis of Single‐Atom Heterogeneous Catalysts. Issue 4 (29th December 2022) - Moragues, Thomas; Mitchell, Sharon; Faust Akl, Dario; Pérez-Ramírez, Javier; deMello, Andrew
Abstract : Wet chemical approaches are among the most versatile and scalable strategies for preparing single‐atom heterogeneous catalysts (SACs). However, despite their broad application, the synthesis of SACs via these routes remains largely ad hoc, with limited attention to the effect of different synthetic parameters on the stabilization of metal species. As a proof of concept, herein, a microfluidic platform is demonstrated for short‐timescale (<10 s), systematic syntheses of SACs via wet impregnation using a range of metal precursor–carrier combinations. The microfluidic environment within rapidly mixed, nanoliter droplets ensures precise control of the concentrations and residence times of the support particles in the metal precursor solutions. This enables the rapid assessment of the influence of the metal precursor concentration on the uptake and dispersion of the adsorbed metal species, as demonstrated for the synthesis of palladium and platinum SACs based on a high‐surface form of graphitic carbon nitride (C3 N4 ). Extension to SACs based on other metals (Ni) and relevant carriers (N‐doped carbon, γ‐alumina) confirms the generality of the synthesis method. The microfluidic approach opens possibilities for high‐throughput parameter screening and mechanistic studies in the design of heterogeneous single‐atom catalysts. Abstract : Droplet‐based microfluidic synthesis of single‐atom catalysts (SACs) takes advantage of the fast mixing and high control over mass transport offered at small scales. These features enable the short‐timescale and reproducible synthesis of diverse SACs. The developed approach presents opportunities for high‐throughput screening of parameter spaces to enhance the discovery and understanding of SACs.